Genus Schismatothele Karsch, 1879 (Araneae, Theraphosidae): taxonomic notes and seven new species description - Moeller, Wolf [UNESP] (2023)
Seven new species of Schismatothele Karsch, 1879 (Araneae, Theraphosidae) are described, almost doubling the diversity of the genus: S. caeri sp. nov.; S. caiquetia sp. nov.; S. merida sp. nov.; S. moonenorum sp. nov.; S. quimbaya sp. nov.; S. timotocuica sp. nov. and S. wayana sp. nov. An identification key for all species of Schismatothele (except S. kastoni) is presented, as well as a complementary diagnosis for the genus. Also, a standardized nomenclature is proposed to describe the prolateral keels of male palpal bulbs of species of Schismatothele.